Evaluation of BMP-2, VEGF, and Vitamin D Receptor Levels in the Ligamentum Flavum of Patients with Lumbar Spinal Stenosis and Disc Herniation - Ertugrul, Bilal; Akgun, Bekir; Artas, Gokhan; Erol, Fatih Serhat; Demir, Fatih (Turkish Neurosurgical Soc, 2022)
AIM: To histopathologically evaluate and compare bone morphogenetic protein (BMP)-2, vascular endothelial growth factor (VEGF), and vitamin D receptor (VDR) levels in the ligamentum flavum (LF) of patients with lumbar spinal stenosis (LSS) and lumbar disc MATERIAL and METHODS: Surgical specimens of the LF in 25 patients who underwent surgery for LDH and 25 patients who underwent surgery for LSS were examined histopathologically. The prevalence and severity of BMP-2, VEGF, and VDR immunoreactivity were evaluated to create histoscores (prevalence x severity), which were compared between groups. RESULTS: The mean BMP-2 histoscore was similar in both groups. In the LSS group, the mean VEGF histoscore was significantly higher and the mean VDR histoscore was significantly lower. CONCLUSION: Elevated VEGF and decreased VDR levels in the LF in LSS are associated with more intense inflammation and chronic process of the disease. The prominent expression of BMP-2 in the LF in both diseases suggests that BMP-2 might be affected by inflammation regardless of chronic pressure and degeneration.
Keywords: Lumbar disc herniation; Spinal stenosis; BMP-2; VEGF; VDR